Sanitation and Water for All : Priority Actions for Sector Financing - World Bank (World Bank, Washington, DC, 2017)
The global commitment to bring universal access to safely managed water supply and sanitation by 2030 set by the Sustainable Development Goals (SDGs) poses an unprecedented challenge. Strong political leadership will be required to bring about sector-wide changes in governance and building technical and administrative capacity at scale. This will pave the way for building, operating, and maintaining cost-effective infrastructure to supply improved and sustained services. The current model of sector finance is insufficient for reaching thee goals. Four interlinked priority actions should be taken to tackle this challenge: (1) make more efficient use of existing resources; (2) use public funds in a more targeted manner; (3) attract domestic commercial finance; and (4) focus on de-risking the sector. Through these steps, countries will be able to leverage each dollar of public funds to crowd in commercial finance, which will have significant and long-term benefits for the sector. Countries should aim to slowly and incrementally introduce commercial finance to the sector, and can ease the transition through a range of available tools.